THE POWER OF ONLINE REVIEWS AND SOCIAL MEDIA INFLUENCERS IN DECODING CAREER CHOICES - Mukherjee, Kausik; Singh, Chandan; Soni, Kartik; Garg, Ankit Kumar; Tripathi, Shivam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the digital age, the process of making career choices has been significantly influenced by the proliferation of online reviews and the rise of social media influencers. This literature review explores the multifaceted role these digital phenomena play in shaping career decisions. Online reviews on platforms like Glassdoor and LinkedIn provide job seekers with critical insights into company cultures, employee experiences, and career advancement opportunities, empowering them to make informed decisions. Concurrently, social media influencers leverage their platforms to offer personalized advice, aspirational narratives, and practical tips on career development, resonating with individuals seeking guidance and validation in their professional journeys. By synthesizing empirical research and theoretical frameworks, this review examines the credibility, reliability, and impact of online reviews, as well as the persuasive techniques and content characteristics of social media influencers. Furthermore, it identifies individual and contextual factors that moderate the influence of these digital sources on career choices. The review highlights gaps in the existing literature and proposes avenues for future research. Practical implications for individuals, employers, and policymakers are discussed, offering strategies for effectively navigating the digital landscape of career guidance. This comprehensive analysis underscores the transformative power of online reviews and social media influencers in decoding career choices, contributing to a deeper understanding of their role in contemporary career decision-making processes.